Migrants in A Synodal Church - James Kumar (Asian Horizons, 2025)
Migrant rights are recognized and honoured in our society. Yet, their misery is a great concern. The Ecclesiastical authority (basing its principles on the Gospel and values of the Kingdom of God) and Civil/Secular authority (basing its principles on human virtues) can combine their effort to bring some sort of solution to the humanitarian crisis of migration. Among many moral and social principles that could be applied towards the solution to the migration crisis, this article recognizes ‘Universal Destiny of Created Goods’ as one of the working principles towards the purpose. The teaching of the principle of the ‘universal destiny of the created goods’ is that migrants and refugees have the right to get access to those resources. The universal destination of created goods requires a common effort. Looking at solving the crisis of migration, the Church should undertake the synodal journey along with organisations like UNO to make a combined effort for the resources be available in one place to be made accessible to others who experience the need for them. A ‘synodal journey’ (of the Church) and the ‘global partnership’ (of UNO) would enhance the realization of ‘the universal destiny of the created goods’ very specially in favour of migrants and refugees.